Short-term, short-changed? A temporal perspective on the implications of academic casualisation for teaching in higher education. Issue 6 (18th August 2022) - Leathwood, Carole; Read, Barbara
ABSTRACT: The increasing casualisation of academic labour over recent years has been noted across the global north. In the UK, this takes a number of forms, including fixed term, hourly paid and zero hours contracts. What tends to characterise them all, however, is a focus on the short-term. In this paper, we draw on a qualitative study with 20 UK-based academics on casualised contracts to consider the implications of the short-term nature of such employment for teaching and pedagogy. We come to this with a temporal perspective, in part in response to Felt's call for a chronopolitical analysis of the changing temporalities of academia. We discuss how short-term temporal logics marked by last-minute or 'just-in-time' modalities can be seen to impact negatively on teaching preparation and pedagogical relationships, raising questions about innovation and criticality, power and in/security, continuity and care.